2016
DOI: 10.1016/j.tics.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Mind-Wandering With and Without Intention

Abstract: The past decade has seen a surge of research examining mind-wandering, but most of this research has not considered the potential importance of distinguishing between intentional and unintentional mind-wandering. However, a recent series of papers has demonstrated that mind-wandering reported in empirical investigations frequently occurs with and without intention, and more critically, that intentional and unintentional mind-wandering are dissociable. This emerging literature suggests that to increase clarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
306
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 362 publications
(338 citation statements)
references
References 96 publications
29
306
1
2
Order By: Relevance
“…Most importantly, participants in the Gyurkovics et al (2017) study reported only whether their thoughts were on-task or off-task, which made it difficult to ascertain what proportion of taskunrelated thoughts involved truly spontaneous (i.e., unintended) rather than intentional mindwandering (see Smallwood & Schooler, 2015;Seli, Risko, Smilek & Schacter, 2016).…”
Section: Cdr-based Classification Used By Gyurkovics Et Al (2017) Amentioning
confidence: 99%
“…Most importantly, participants in the Gyurkovics et al (2017) study reported only whether their thoughts were on-task or off-task, which made it difficult to ascertain what proportion of taskunrelated thoughts involved truly spontaneous (i.e., unintended) rather than intentional mindwandering (see Smallwood & Schooler, 2015;Seli, Risko, Smilek & Schacter, 2016).…”
Section: Cdr-based Classification Used By Gyurkovics Et Al (2017) Amentioning
confidence: 99%
“…Recent research has shown that mind wandering consists of a complex, multi-faceted pattern involving episodic thought, emotion, executive control and meta-awareness in a component process account [36] featuring intricate combinations of corresponding neural responses [37]. Furthermore, intention during mind wandering has recently been identified as a key dimension with great explanatory power [38][39][40]. Our model is less concerned with such precise specification of the mind-wandering state and instead emphasizes the dynamics of the transitions between different attentional states.…”
Section: A Neural Model Of Mind Wanderingmentioning
confidence: 99%
“…From a different perspective, the distinction between deliberate vs. nondeliberate MW gained increasing interest recently, with deliberate MW being accompanied by elevated FPN activity (4, 9). Considering that deliberate MW is less frequent in demanding tasks (9), the paradigm of Kucyi et al (7) might not have allowed extended periods of intentional MW, resulting in weaker FPN signals.…”
mentioning
confidence: 99%